2007
DOI: 10.1038/nprot.2007.278
|View full text |Cite
|
Sign up to set email alerts
|

A protocol for designing siRNAs with high functionality and specificity

Abstract: Effective gene silencing by the RNA interference (RNAi) pathway requires a comprehensive understanding of the elements that influence small interfering RNA (siRNA) functionality and specificity. These include (i) sequence space restrictions that define the boundaries of siRNA targeting, (ii) structural and sequence features required for efficient siRNA performance, (iii) mechanisms that underlie nonspecific gene modulation and (iv) additional features specific to the intended use (i.e., inclusion of native sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
174
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(178 citation statements)
references
References 45 publications
3
174
0
1
Order By: Relevance
“…To eliminate the characterization of artifacts arising through off-target effects, 3 independent FEN1 silencing conditions were used-2 independent siRNA duplexes (FEN1-2 and FEN1-3) and a FEN1-pool comprised of 4 independent siRNA duplexes (effectively quartering the concentration of each duplex), that has been shown to greatly diminish off-target effects (42)(43)(44)(45)(46). Using fixed and live cell HC-DIM, we showed that diminished FEN1 expression adversely affects overall cell numbers, which presumably occurs through the corresponding increases in cellular cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…To eliminate the characterization of artifacts arising through off-target effects, 3 independent FEN1 silencing conditions were used-2 independent siRNA duplexes (FEN1-2 and FEN1-3) and a FEN1-pool comprised of 4 independent siRNA duplexes (effectively quartering the concentration of each duplex), that has been shown to greatly diminish off-target effects (42)(43)(44)(45)(46). Using fixed and live cell HC-DIM, we showed that diminished FEN1 expression adversely affects overall cell numbers, which presumably occurs through the corresponding increases in cellular cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…A more rigorous approach is to demonstrate rescue with an "immunized" transgene that contains silent mutations in the siRNA-binding site, thus preventing RNAi silencing. Last, off-target effects are dose dependent (Birmingham et al, 2007), and therefore the minimal dose required to obtain sufficient knockdown should be used.…”
Section: Seed Sequence Of Sirnas Is Critical For Predicting Off-targementioning
confidence: 99%
“…In addition, endoribonucleolytically digested small overlapping dsRNA fragments (esiRNAs) and small hairpin RNA libraries (shRNAs) encoded on vector backbones can be used for systematic knockdown analysis [10,22]. Chemically synthesized siRNAs and esiRNAs are introduced into the cells by liposomal transfection, electroporation or by linking RNAs to guiding peptides [9,[23][24][25][26].These siRNAs can be further chemically modified to increase stability and transfection efficiency [27][28][29]. Furthermore, lenti-, retroor adenoviral particles carrying DNA vectors that encode shRNAs can be used to transduce mammalian cells that are difficult to transfect with other methods [10,30,31].…”
Section: Introductionmentioning
confidence: 99%